Seasonal habitat selection and temporal activity patterns determine the structure of bat assemblages in Dhana Biosphere Reserve, Jordan (Mammalia: Chiroptera). Issue 1 (2nd January 2019) - Abed, Omar A.; Abu Baker, Mohammad A.; Amr, Zuhair S.
Abstract : We measured species richness, diversity, and diel activity patterns of insectivorous bats at four sites within Dhana Biosphere Reserve. A total of seven species belonging to five families at varying species compositions were recorded. Four to six species were present at these sites and total diversity ranged between 0.32 at Ain Lahtha and 0.65 at Al Khararah. Overall frequency of passes was highest at Shaq Kalbeh. The Common Pipistrelle, Pipistrellus pipistrellus, was the most prevalent at three sites, followed by the Arabian Horseshoe Bat, Rhinolophus clivosus, and Botta's Serotine, Eptesicus bottae . Natterer's Bat, Myotis nattereri, and the European Free-tailed Bat, Tadarida teniotis, occurred at low abundance. The Lesser Horseshoe Bat, Rhinolophus hipposideros, occurred at a higher abundance within Finan site (arid site at lower altitude), whereas the Egyptian Mouse-tailed Bat, Rhinopoma cystops, was restricted to Finan. The overall mean number of bat passes was not significantly different between sites. Average seasonal species diversity was low during winter (none at Ain Lahtha and Shaq Kalbeh) and highest during summer (0.68 at Al Kharrarah). Seasonal activity patterns for each site in terms of frequencies of bat passes on an hourly basis are given.